Effect of porosity on dielectric properties of ZnO ceramics. Issue 4 (April 2020) - de Sousa e Silva, Raphael Lucas; Franco, A.
Abstract: In this study we investigated the effect of porosity level on the dielectric properties and conductivity of ZnO ceramic samples sintered by pressure-less solid-state reaction method. The relative permittivity ( ε r ′ ) and, tangent loss value decreased gradually with increasing porosity, being 1.9 × 10 5 and 35.6 × 10 3 for sample with low porosity and high porosity level, respectively at room temperature. Also the tangent loss decreases with increasing porosity level being quite high (∼10 2 ) at low frequencies and, low (∼10 −1 ) at high frequencies. The complex part of the relative permittivity results could be fitted to the Maxwell-Wagner (MW) model suggesting a poly-dispersive relaxation time. The frequency dependence-ac conductivity determined by means of dielectric data was strongly dependent of the porosity level. It decreases sharply with increasing porosity level is frequency independent- up to ∼10 4  − 10 5  Hz followed by an abrupt increase at higher frequencies. These data were discussed in terms ZnO defects such as Zn interstitial and oxygen vacancies present in the grain boundaries.